1995
DOI: 10.1080/0950069950170507
|View full text |Cite
|
Sign up to set email alerts
|

Children's knowledge of the earth's shape and its gravitational field

Abstract: One hundred and eight children aged between seven and 11 took part in a cross-sectional study of the development of their concepts of the Earth and the direction of its gravitational field. A new form of 'Earth drawing classification' (EDC) was found to be drawn by 36% of the sample, together with the five classifications established in earlier work. This new EDC is conceptually contradictory and appears to be a critical development stage. It is the result of the pupils' attempts to reconcile scientific inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…America is like a lower story (sic) compared with Europe and that to reach America the Sun had to cross the sea by a tunnel which pierced what formed the floor of Europe and the roof of America. (1929: 296) In more recent years, and partly in association with the rise of the constructivist or "alternative frameworks movement" (e.g., Driver et al, 1994;Duit & Treagust, 2003), children's ideas about the shape of the Earth and the day and night cycle have received a great deal more attention (Baxter, 1989;Diakidoy, Vosniadou, & Hawks, 1997;Jones, Lynch, & Reesink, 1987;Nussbaum, 1985;Samarapungavan, Vosniadou, & Brewer, 1996;Schoultz, Säljö, & Wyndhamn, 2001;Vosniadou & Brewer, 1992 and the positive effects of formal intervention at school reconsidered (Arnold, Sarge, & Worrall, 1995;Diakidoy & Kendeou, 2001; Kikas, 1998;Nussbaum & Sharoni-Dagan, 1983;Sharp, 1999;Sneider & Ohady, 1998).…”
Section: Review Of Literaturementioning
confidence: 99%
“…America is like a lower story (sic) compared with Europe and that to reach America the Sun had to cross the sea by a tunnel which pierced what formed the floor of Europe and the roof of America. (1929: 296) In more recent years, and partly in association with the rise of the constructivist or "alternative frameworks movement" (e.g., Driver et al, 1994;Duit & Treagust, 2003), children's ideas about the shape of the Earth and the day and night cycle have received a great deal more attention (Baxter, 1989;Diakidoy, Vosniadou, & Hawks, 1997;Jones, Lynch, & Reesink, 1987;Nussbaum, 1985;Samarapungavan, Vosniadou, & Brewer, 1996;Schoultz, Säljö, & Wyndhamn, 2001;Vosniadou & Brewer, 1992 and the positive effects of formal intervention at school reconsidered (Arnold, Sarge, & Worrall, 1995;Diakidoy & Kendeou, 2001; Kikas, 1998;Nussbaum & Sharoni-Dagan, 1983;Sharp, 1999;Sneider & Ohady, 1998).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Nussbaum and Novak (1976) investigated elementary school children's ideas about the Earth's shape and gravity and found that many of them believed that objects fall 'downwards', as distinct from 'towards the centre of the Earth' and as a result some students could not understand why people did not fall off the bottom of the Earth. Later studies indicated that this idea was widespread and could often persist up to eighth grade level (Nussbaum 1979, Sneider and Pulos 1983, Arnold et al 1995.…”
Section: Students' Conceptions Of Gravitymentioning
confidence: 99%
“…Drawings are often used when our primary research interest is children's conceptions (e.g., Arnold, Sarge & Worall, 1995;Dove, Everett & Preece, 1999;Halldén et al, 2002;Klein, 1982;Sneider & Pulos, 1983;Vosniadou & Brewer, 1992). This tradition has recently received methodological and theoretical criticism.…”
Section: Drawings As Representations Of Children's Conceptions Introdmentioning
confidence: 99%